2018
DOI: 10.1186/s12864-018-5235-3
|View full text |Cite
|
Sign up to set email alerts
|

Coordinate regulation of long non-coding RNAs and protein-coding genes in germ-free mice

Abstract: BackgroundLong non-coding RNAs (lncRNAs) are increasingly recognized as regulators of tissue-specific cellular functions and have been shown to regulate transcriptional and translational processes, acting as signals, decoys, guides, and scaffolds. It has been suggested that some lncRNAs act in cis to regulate the expression of neighboring protein-coding genes (PCGs) in a mechanism that fine-tunes gene expression. Gut microbiome is increasingly recognized as a regulator of development, inflammation, host metabo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 86 publications
0
37
0
Order By: Relevance
“…In studies conducted by Dejea and colleagues [59], pks + E. coli were found to work synergistically with enterotoxigenic Bacteroides fragilis (ETBF) to cause increased DNA damage and increased tumor formation in a mouse model of CRC. This DNA damage was accompanied by a heightened inflammatory response that was necessary, but not RNA-seq lncRNAs in the mouse duodenum, jejunum, ileum, and colon were altered in GF mice when compared to conventional mice [118] Murine gut microbiome Mice Pathways related to GPCR signaling and TGF signaling RNA-seq sufficient, for increased colon tumor formation. The increased tumorigenesis was also highly dependent on the presence of both colibactin and B. fragilis toxin (BFT).…”
Section: The Genomementioning
confidence: 98%
See 1 more Smart Citation
“…In studies conducted by Dejea and colleagues [59], pks + E. coli were found to work synergistically with enterotoxigenic Bacteroides fragilis (ETBF) to cause increased DNA damage and increased tumor formation in a mouse model of CRC. This DNA damage was accompanied by a heightened inflammatory response that was necessary, but not RNA-seq lncRNAs in the mouse duodenum, jejunum, ileum, and colon were altered in GF mice when compared to conventional mice [118] Murine gut microbiome Mice Pathways related to GPCR signaling and TGF signaling RNA-seq sufficient, for increased colon tumor formation. The increased tumorigenesis was also highly dependent on the presence of both colibactin and B. fragilis toxin (BFT).…”
Section: The Genomementioning
confidence: 98%
“…Less is known about the interaction between lncRNAs and the gut microbiome, probably because of difficulties in identifying the function of most lncRNAs. In one study, Dempsey and colleagues [118] found that the expression of lncRNAs in the mouse duodenum, jejunum, ileum, and colon was altered in the absence of gut microbes. Most of the DNA sequences encoding these lncRNAs were located in intergenic regions or in the introns of protein-coding genes, and the lncRNAs were predicted to function in regulating the expression of those genes.…”
Section: The Gut Microbiome and Non-coding Rnasmentioning
confidence: 99%
“…Most of the lncRNAs which were found to be regulated by gut microbiome were present in an essential metabolic organ, namely, the jejunum. Overall, this is the first study that demonstrated that the gut microbiome is important for the lncRNA expression in the various metabolic and other organs (Dempsey et al, 2018). These studies implicate a potential role played by the gut microbiome in regulation of lncRNA expression.…”
Section: Noncoding Rnamentioning
confidence: 54%
“…The noncoding RNA (ncRNA) are RNA transcripts that are not translated into the proteins (Dempsey et al, 2018). The alterations in ncRNA have been known to contribute to various diseases such as obesity, diabetes, neurodegenerative diseases, liver diseases, and lung diseases (Devaux and Raoult, 2018).…”
Section: Noncoding Rnamentioning
confidence: 99%
See 1 more Smart Citation